Evaluation of different metal salt solutions for the preparation of solar cells with wide-gap Cu2ZnGeSxSe4−x absorbers. Issue 1 (22nd December 2016) - Schnabel, T.; Seboui, M.; Ahlswede, E.
Abstract : In this work, thin-film solar cells with a kesterite-type Cu2 ZnGeS x Se4− x (CZGSSe) absorber were prepared from four different metal salt solutions. Abstract : In this work, thin-film solar cells with a kesterite-type Cu2 ZnGeS x Se4− x (CZGSSe) absorber were prepared from four different metal salt solutions. Their high band gap makes them an interesting material for tandem solar cells. The structural and morphological properties of the absorbers are compared with an additional focus on the electrical properties of the resulting thin-film solar cells. Efficiencies exceeding 5% could be demonstrated.